2012
DOI: 10.1111/acel.12004
|View full text |Cite
|
Sign up to set email alerts
|

Increased age of transformed mouse neural progenitor/stem cells recapitulates age‐dependent clinical features of human glioma malignancy

Abstract: Increasing age is the most robust predictor of greater malignancy and treatment resistance in human gliomas. However, the adverse association of clinical course with aging is rarely considered in animal glioma models, impeding delineation of the relative importance of organismal versus progenitor cell aging in the genesis of glioma malignancy. To address this limitation, we implanted transformed neural stem/progenitor cells (NSPCs), the presumed cells of glioma origin, from 3 and 18month old mice into 3 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 43 publications
(64 reference statements)
1
22
0
Order By: Relevance
“…Aged mouse NPCs that have been oncogenically transformed by overexpression of Ras and simultaneous abrogation of tumor suppressor proteins p53 and Rb, form more malignant gliomas in vivo than their younger counterparts (Mikheev et al ., 2009). The negative impact of increased age on outcome in this model is cell intrinsic; the age of transplanted cells, but not the host age, determines the degree of malignancy based on survival, invasiveness, genomic stability, and responses to genotoxic and hypoxic stress (Mikheev et al ., 2012). These data suggest that normal aging predisposes NPCs to increased malignant potential.…”
Section: Oncogenesis and The Aging Neural Progenitor Cellmentioning
confidence: 99%
See 3 more Smart Citations
“…Aged mouse NPCs that have been oncogenically transformed by overexpression of Ras and simultaneous abrogation of tumor suppressor proteins p53 and Rb, form more malignant gliomas in vivo than their younger counterparts (Mikheev et al ., 2009). The negative impact of increased age on outcome in this model is cell intrinsic; the age of transplanted cells, but not the host age, determines the degree of malignancy based on survival, invasiveness, genomic stability, and responses to genotoxic and hypoxic stress (Mikheev et al ., 2012). These data suggest that normal aging predisposes NPCs to increased malignant potential.…”
Section: Oncogenesis and The Aging Neural Progenitor Cellmentioning
confidence: 99%
“…In vitro studies show that actively cycling NPCs derived from the aged mouse forebrain migrate at similar rates to actively cycling NPCs from the young adult mouse forebrain, while noncycling cells migrate more slowly with age (Stoll et al ., 2011a). By contrast, in a syngeneic transplant model, aging-transformed NPCs demonstrated markedly increased invasive potential in vitro and in vivo compared with young transformed NPCs (Mikheev et al ., 2012). These findings suggest that age-related differences in normal NPCs that are either amplified or ‘unmasked’ upon oncogenic transformation result in age-related increases in invasive potential in mouse models.…”
Section: Interactions Between Tumor-initiating Cells and The Surroundmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent studies suggest the accumulation of DNA damage (as indicated by genomic marks like g-H2AX and 53BP1) in stem-cell populations like the hematopoietic system (Rossi et al 2007) and in the dentate gyrus neurogenic niche (DeCarolis et al 2014). Other reports have suggested the accumulation of mutations in DNA and genomic instability within the NSC pool with age (Mikheev et al 2012;Dong et al 2014) but additional research is needed. Other cell-intrinsic facets of aging have been characterized in peripheral stem-cell pools (LopezOtin et al 2013), including decreased telomerase activity associated with shortened telomeres (Sahin and Depinho 2010), epigenetics changes (Webb et al 2013;Brunet and Berger 2014), and asymmetric nonrandom chromosome segregation (Charville and Rando 2011).…”
Section: Cell-intrinsic Changesmentioning
confidence: 99%